Implementation of Agile Methodology in the Design and Development of Web-Based New Student Admission Information System - Kaazhim, Dzakiyyah Al; Nugroho, Nicolaus Euclides Wahyu (LPPM Institut Teknologi Telkom Purwokerto, 2024)
The infrastructure supporting communities and educational institutions is necessary for the Industry 4.0 era to increase the productivity of educational institutions. The new student registration process at TK Al-Fath is still traditional. It has several shortcomings, such as repeated visits by parents during registration, repetitive information delivery, and unorganized documents, leading to difficulties in data summarization. A web-based system is required to assist TK Al-Fath and prospective students' parents in the new student admission process. This information system will be developed using the Agile development methodology, which will include stages of planning, implementation, software testing, documentation, and deployment. By applying the Agile methodology, the developed information system meets user needs and can be quickly adapted according to changes and feedback received during the development process. This system is limited to serving as an information and registration center, developed from observation, discussion, and literature study. In the final stage, Blackbox testing and User Acceptance Testing (UAT) were conducted. In the Blackbox testing, there were nine functionality testing scenarios, all of which resulted in a 'Successful' status after being tested by 20 respondents. The design and development of the Web-Based New Student Admission Information System at TK Al-Fath were completed and accepted by users, with a total UAT percentage of 93.58%, falling into the 'Very Good' category.